2019
DOI: 10.1038/s41562-019-0749-5
|View full text |Cite
|
Sign up to set email alerts
|

Socially transmitted placebo effects

Abstract: Medical treatments typically occur in the context of a social interaction between healthcare providers and patients. Although, decades of research have demonstrated that patients’ expectations can dramatically impact treatment outcomes, less is known about the influence of providers’ expectations. Here, we systematically manipulated providers’ expectations in a simulated clinical interaction involving administration of thermal pain and found that patients’ subjective experiences of pain were directly modulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 95 publications
0
47
0
2
Order By: Relevance
“…Because investigators were not blinded to the time of randomization, this might suggest that the clinician-rated assessments (MADRS; CGI scales) may have been subject to some level of bias related to their awareness of when improvements could be expected. Although the patients were blinded to the placebo lead-in study feature, a similar pattern was observed for the patient-reported assessments (HADS scales; PGI), which might hypothetically be explained by ‘socially transmitted’ placebo effects ( Chen et al ., 2019 ), that is, investigators’ inadvertent and subconscious communication of their own expectations to the patient, and/or by patients not expecting an effect immediately after the first (placebo-) IV based on their previous experience or knowledge about antidepressant (SSRI) treatment. Altogether, such limitations may have led to reduced assay sensitivity, hence attenuating any treatment differences between vortioxetine and placebo, in this already small study.…”
Section: Discussionmentioning
confidence: 69%
“…Because investigators were not blinded to the time of randomization, this might suggest that the clinician-rated assessments (MADRS; CGI scales) may have been subject to some level of bias related to their awareness of when improvements could be expected. Although the patients were blinded to the placebo lead-in study feature, a similar pattern was observed for the patient-reported assessments (HADS scales; PGI), which might hypothetically be explained by ‘socially transmitted’ placebo effects ( Chen et al ., 2019 ), that is, investigators’ inadvertent and subconscious communication of their own expectations to the patient, and/or by patients not expecting an effect immediately after the first (placebo-) IV based on their previous experience or knowledge about antidepressant (SSRI) treatment. Altogether, such limitations may have led to reduced assay sensitivity, hence attenuating any treatment differences between vortioxetine and placebo, in this already small study.…”
Section: Discussionmentioning
confidence: 69%
“…In studies in which the participant is not told the treatment assignment, but research staff in contact with the participants are aware of the treatment assignment, the expectation of the research staff has been well documented to be transmitted to the participant, with a major impact on treatment effects. 36 , 85 , 107 Therefore, single-blind studies can be viewed as essentially unblinded.…”
Section: Preventing False-positive Studies: Randomization Blindinmentioning
confidence: 99%
“… 15 Although rarely appreciated, provider expectations of an intervention may be non-verbally communicated to the patients and impact outcome. 78 , 79 Semantic processing continues in an altered state of consciousness, 80 , 81 with some patients later recalling things said to them while comatose 82 that may lead to an unintended potential for harm. Although a call for the mindful choice of words with the critically ill dates back to 1969, 15 clinical adoption has been limited.…”
Section: Implications Of Psychological Milieu For Critically Ill Patimentioning
confidence: 99%